Students' Perceptions of Educational Planning Course Curriculum Development - Ningrum, Tia Ayu; Anugrah, Septriyan; Azizah, Zahratul; Wildanah, Fifin; Budi Utama, Hendri; Lutfiani, Lutfiani (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
Educational planning is one of the compulsory subjects to achieve one of the educational administration graduate profiles, namely becoming an educational planner. However, with the development of science and technology and adapting it to the current needs of students, it is necessary to conduct research for curriculum development for educational planning courses.For this reason, the purpose of this paper is to find out student perceptions of student perceptions of curriculum development for the Education Planning Course. The method used is Mix (mixture) that is qualitative and qualitative. Data collection using questionnaires, documentation, observation and interviews. The results of the research show that the Education Planning Course needs to be developed. Good learning is project-based using actual and updated data. an area. Good learning uses digital media or applications that make it easier to calculate and obtain valid data and reduce human error.